Analysis of Affecting Factors Difficulties of Learning Mathematics in Elementary Age Children - Fia Alifah Putri; Cut Maslina Muthia; Irna Yunita; Noni Indah Rini; Widya Aprisah Harahap (Journal of Contemporary Islamic Primary Education, 2022)
This study aims to analyze the factors that influence the difficulty of learning mathematics in elementary age children. The focus of this research is on informants with the initials MI, students of SD Negeri 18 Sisumut. The collection of information used in this observation is research, interviews, Draw a Person-IQ tests, and the V.I.I Learning Difficulty Scale test. From the results of research and interviews, students with the initials MI often play and are less able to do the assignments given. The process of identifying student learning difficulties using the Draw a Person-IQ test, and the V.I.I. Learning Difficulty Scale test. After recognizing students' learning difficulties using this scale, it was found that MI students had learning difficulties in the areas of writing and reading. By knowing the types of learning difficulties, teachers can choose the right type of intervention, effective and efficient to be given in helping students overcome learning difficulties.